Validity of Visual Evoked Response in measuring Ethambutol induced Optic neuritis in Tuberculosis Patients: Evaluation using Receiver Operating Characteristic (ROC) curves - Singh, Satendra; Sushma, Sood; Jyoti, Sethi; ., Beena (Pakistan Journal of Physiology, 2007)
Background: Significant vision loss can occur during treatment with Ethambutol in tuberculosis (TB) patients. Visual Evoked Response (VER) is often used to detect this subclinical visual impairment even before the appearance of symptoms. We assessed the usefulness of three V.E.R parameters- P100 latency, amplitude and interocular difference for the early diagnosis of ethambutol-induced optic neuritis (ON). Methods: This study was carried out on 60 newly diagnosed adult cases of tuberculosis aged between 20-50 years who were randomly assigned into two groups of 30 each. Nonparametric Receiver Operating Characteristic (ROC) analysis was used to evaluate the validity of VER indexes. Results: At a cutoff pint of 116 ms sensitivity for the diagnosis of ON was 77.8% and specificity was 81.1%.Results of the application of Bayes’s theorem showed that 87% of the patients scoring 116 ms or higher would actually have ethambutol-induced ON and 99% of those scoring less than 116 ms would not have ON. The best area under curve (AUC) for ROCs, an index of diagnosing accuracy, was 0.91 for P100 latency, suggesting very good accuracy. Conclusions: The results suggest that P100 latency gives the best results for ON screening in ethambutol treated patients. Amplitude and interocular difference were reasonable alternatives. Measurement of P100 latency of V.E.R is a valuable tool which can be used more easily than clinical examination in detecting subclinical ethambutol-induced ON.